PERAN GREEN TRUST DAN GREEN SATISFACTION MEMEDIASI HUBUNGAN GREEN IMAGE DENGAN GREEN LOYALTY - Astuti, Ni Luh Gde Sari Dewi; Sukaatmadja, I Putu Gde (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
Green hotel has become a branding and strategy in winning business competition, if using environmentally friendly energy. This study aims to explain the relationship green image with green trust, green image with green satisfaction, green trust with green loyalty, green satisfaction with green loyalty, green image with green loyalty, and to explain the role of green trust and green satisfaction in mediating green image relationship with green loyalty. The population in this study are the guests who have been staying at Hotel Bali Tropic Resort & Spa (minimum 2 times stay in the period of 2013-2017) with sample size of 100 respondents. This research uses analysis technique PLS (Partial Least Square). This study found that green image has a positive relationship with green trust, green satisfaction, and green loyalty. Green trust and green satisfaction have a positive relationship with green loyalty. Green trust and green satisfaction are able to mediate partially and have a positive relationship with green loyalty.